Absorptive capacity between knowledge sharing and agile software process improvement success in Indonesian telecommunication company - Kelana, Bayu; Rahman, Titik Khawa Binti Abdul; Arsy, Cyntia Fushila; Rahmatina, Ulya Dini (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study investigates the role of absorptive capacity as a mediator in the relationship between knowledge sharing and agile software process improvement. Data was collected from 99 participants with experience in agile software development teams at two agile-based Indonesian telecommunication companies. The analysis was conducted using the PLS-SEM method and an embedded two-stage approach. The results demonstrate that absorptive capacity fully mediates the impact of knowledge sharing on the success of agile software process improvement (SPI). However, knowledge sharing alone does not significantly enhance agile SPI success. These findings highlight the importance of absorptive capacity in leveraging knowledge sharing to achieve agile SPI success, particularly within agile software development teams in Indonesian telecommunication companies.